Right Ventricular Longitudinal Strain Is Depressed in a Bovine Model of Pulmonary Hypertension. (May 2016) - Bartels, Karsten; Brown, R. Dale; Fox, Daniel L.; Bull, Todd M.; Neary, Joseph M.; Dorosz, Jennifer L.; Fonseca, Brian M.; Stenmark, Kurt R.
Abstract : BACKGROUND: Pulmonary hypertension and resulting right ventricular (RV) dysfunction are associated with significant perioperative morbidity and mortality. Although echocardiography permits real-time, noninvasive assessment of RV function, objective and comparative measures are underdeveloped, and appropriate animal models to study their utility are lacking. Longitudinal strain analysis is a novel echocardiographic method to quantify RV performance. Herein, we hypothesized that peak RV longitudinal strain would worsen in a bovine model of pulmonary hypertension compared with control animals. METHODS: Newborn Holstein calves were randomly chosen for induction of pulmonary hypertension versus control conditions. Pulmonary hypertension was induced by exposing animals to 14 days of hypoxia (equivalent to 4570 m above sea level or 430 mm Hg barometric pressure). Control animals were kept at ambient pressure/normoxia. At the end of the intervention, transthoracic echocardiography was performed in awake calves. Longitudinal wall strain was analyzed from modified apical 4-chamber views focused on the RV. Comparisons between measurements in hypoxic versus nonhypoxic conditions were performed using Student t test for independent samples and unequal variances. RESULTS: After 14 days at normoxic versus hypoxic conditions, 15 calves were examined with echocardiography. Pulmonary hypertension was confirmed by right heart catheterization and associated with reduced RV systolic function. Mean systolic strain measurements were compared in normoxia-exposed animals ( n = 8) and hypoxia-exposed animals ( n = 7). Peak global systolic longitudinal RV strain after hypoxia worsened compared to normoxia (−10.5% vs −16.1%, P = 0.0031). Peak RV free wall strain also worsened after hypoxia compared to normoxia (−9.6% vs −17.3%, P = 0.0031). Findings from strain analysis were confirmed by measurement of tricuspid annular peak systolic excursion. CONCLUSIONS: Peak longitudinal RV strain detected worsened RV function in animals with hypoxia-induced pulmonary hypertension compared with control animals. This relationship was demonstrated in the transthoracic echocardiographic 4-chamber view independently for the RV free wall and for the combination of the free and septal walls. This innovative model of bovine pulmonary hypertension may prove useful to compare different monitoring technologies for the assessment of early events of RV dysfunction. Further studies linking novel RV imaging applications with mechanistic and therapeutic approaches are needed. Abstract : Published ahead of print March 11, 2016